Approaching Environmental Sustainability: Perceptions of Self-Efficacy and Changeability. Issue 3 (3rd April 2017) - Schutte, Nicola S.; Bhullar, Navjot
ABSTRACT: This paper describes a model focused on the role of self-efficacy and belief in changeability of behavior in motivating environmentally sustainable behavior. The model was tested in two studies. The first study found that participants who had greater self-efficacy for sustainability behavior and a greater belief in their changeability of sustainability behavior had a higher level of approach motivation toward sustainability behavior and reported more such actual behavior. The second study investigated the effect of brief interventions intended to increase perception of self-efficacy for sustainability-related purchasing and changeability of sustainability-related purchasing. The intervention that focused on enhancing self-efficacy for making sustainability-related purchases had the strongest impact on intention to purchase. These findings have implications for interventions intended to change behavior related to environmental sustainability.